2005
DOI: 10.1124/dmd.105.007112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the in Vitro Metabolism of Selective Androgen Receptor Modulator Using Human, Rat, and Dog Liver Enzyme Preparations

Abstract: ABSTRACT:Compound S4 [S-3-(4-acetylamino-phenoxy)-2-hydroxy-2-methyl-N-(4-nitro-3-trifluoromethyl-phenyl)-propionamide] is a novel nonsteroidal selective androgen receptor modulator that demonstrates tissue-selective androgenic and anabolic effects. The purpose of this in vitro study was to identify the phase I metabolites, potential species differences in metabolism, and the cytochromes P450 (P450s) involved in the phase I metabolism of S4 using 14 C-S4, recombinant P450s, and other liver enzyme preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…4A shows the proposed fragmentation ions of S-26. Similar metabolic pathways of SARMs were reported also previously by our laboratory (23)(24)(25). The product ion at m/z 299 corresponds to a cleavage of the bond between the chiral carbon and methylene carbon with loss of a methyl group.…”
Section: Identification Of Major Metabolites Of S-26 In Rat Urine Andsupporting
confidence: 58%
See 2 more Smart Citations
“…4A shows the proposed fragmentation ions of S-26. Similar metabolic pathways of SARMs were reported also previously by our laboratory (23)(24)(25). The product ion at m/z 299 corresponds to a cleavage of the bond between the chiral carbon and methylene carbon with loss of a methyl group.…”
Section: Identification Of Major Metabolites Of S-26 In Rat Urine Andsupporting
confidence: 58%
“…Among all tissues, the thyroid gland accumulated the highest percentage of radioactivity at all three time points, suggesting that S-26 was extensively de-iodinated in vivo, which was further confirmed by our metabolism studies using rat urine and feces. The deiodination of S-26 represented a different metabolic pathway of SARMs comparing to the metabolism studies previously reported by our laboratory (23)(24)(25). The high accumulation of radioactivity by GI tract and a large proportion of radioactivity in urine are also indications of release of free iodine from the parent drug in vivo.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous in vitro metabolism studies (Gao et al, 2006b) have identified species differences between rats and dogs in the metabolism of S-4. Thus, we also further characterized and compared the metabolic profiles of S-4 in these two species.…”
Section: S-3-(4-acetylamino-phenoxy)-2-hydroxy-2-methyl-n-(4-nitro-3-mentioning
confidence: 99%
“…S1, S4, and C6 share similar metabolic labile sites, including the amide bond and the A-ring nitro group, as amide bond hydrolysis and nitro reduction were identified as the major metabolic pathway (Fig. 6) both in vivo (data not published) and in vitro (60,61). All three derivatives are eliminated exclusively through hepatic metabolism.…”
Section: Bothmentioning
confidence: 99%